Industry 4.0 implementation factors for agri-food and manufacturing SMEs in Central and Eastern Europe - Varbanova, Monika; Dutra de Barcellos, Marcia; Kirova, Milena; De Steur, Hans; Gellynck, Xavier (Serbian Journal of Management, 2023)
In partnership with the project “Possibilities and barriers for Industry 4.0 implementation in SMEs in V4 countries and Serbia” - funded by the Visegrad Fund, the authors conducted a survey with 124 small and medium enterprises (SMEs) in Central and Eastern Europe. Respondents (middle and top managers) from Bulgaria, Serbia, Hungary, Poland, Slovakia, and the Czech Republic were questioned about strategic factors affecting digitalization. We analyze theoretical factors based on literature review and if they are valid in the managerial context, not only for manufacturing, but also for the agri-food sector, where digital transformation (Agriculture 4.0) is considered to be in its infancy. Results indicate 21 variables that were aggregated to form five (5) strategic factors (Leadership, Management Strategy, Organizational culture, Business environment and Circular economy) with key importance for Industry 4.0 implementation in the organizations. The comparison based on Exploratory Factor Analysis between the manufacturing and agri-food sector results in statistical differences for all five factors. This study contributes to the management literature, and the identified factors can guide companies to develop a business model to be implemented in SMEs companies in their digital transition.
Keywords: Industry 4.0; SMEs; digitalization; agri-food sector; smart manufacturing; strategic factors; survey